2015
DOI: 10.1002/hep.27722
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the genotype and integration patterns of hepatitis B virus in early‐ and late‐onset hepatocellular carcinoma

Abstract: Early-onset hepatocellular carcinoma (HCC) accounts for 15%-20% of total HCC cases in Asia, and the incidence is increasing. The low frequency of cirrhosis and poor prognosis of early-onset HCC suggests that its mechanisms may differ from late-onset HCC. Although hepatitis B virus (HBV) infection is epidemiologically associated with HCC, the role of HBV in early-onset HCC remains poorly understood. Here, we report a comparative study of HBV subgenotypes and integration in early-( £ 30) and late-onset (70) HBV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 42 publications
7
91
1
3
Order By: Relevance
“…Mechanisms for early-onset (B30 years) HCC may be different from those for late-onset (C70 years) HCC, given the low frequency of liver cirrhosis and poor prognosis in the former. In a comparative study of HBV sub-genotypes and HBV-associated HCC from Shanghai, China, Yan et al found that HBV sub-genotype B2 was predominant in early-onset HCC (mostly without cirrhosis), while C2 was more frequently seen in late-onset HCC [46]. However, in a community-based study from mainland China, HCC-associated mutations were more frequently found in young patients infected with genotype C than in those with genotype B, indicating genotype C might be more apt to cause LC and HCC with increasing age [47].…”
Section: Hbv Genotypes and Clinical Manifestation In Asiamentioning
confidence: 97%
“…Mechanisms for early-onset (B30 years) HCC may be different from those for late-onset (C70 years) HCC, given the low frequency of liver cirrhosis and poor prognosis in the former. In a comparative study of HBV sub-genotypes and HBV-associated HCC from Shanghai, China, Yan et al found that HBV sub-genotype B2 was predominant in early-onset HCC (mostly without cirrhosis), while C2 was more frequently seen in late-onset HCC [46]. However, in a community-based study from mainland China, HCC-associated mutations were more frequently found in young patients infected with genotype C than in those with genotype B, indicating genotype C might be more apt to cause LC and HCC with increasing age [47].…”
Section: Hbv Genotypes and Clinical Manifestation In Asiamentioning
confidence: 97%
“…HBV shows significant enrichment of integration near fragile sites, repetitive regions, CpG islands, and telomeres in tumours compared to non-tumour tissue [84,94]. Over half of the integration events were located in intergenic regions within the chromosomes of the human genome and in repeat sequences such as LINEs, short interspersed nuclear elements, or simple repeats (microsatellites) [94]. Furthermore, chromosomal rearrangements and copy number variations were associated with a large fraction of HBV-related HCCs [43,80], but this can be highly variable [95,96].…”
Section: Hbv Dna Integrationmentioning
confidence: 99%
“…HBV integration is a common phenomenon, even in early-onset HCC, but the conditions between early- and late-onset diseases are rather different. A breakpoint between c-MYC and plasmacytoma variant translocation 1 ( PVT1) , located in the 8q24 gene desert, is frequently detected in early-onset HCC, resulting in overexpression of c-MYC in tumors [103,104]. However, the stage in tumor development when this integration occurs, and how important it may be for HCC, is currently unknown.…”
Section: C-myc and Viral Hepatitis: Playing The Same Tunementioning
confidence: 99%